A study of the Haematological findings, Serum Proteins and Liver function tests in the Natal African in Health and in Amoebiasis - Powell, S J (Adolescent Health Research Institute, 2020)
A notable feature of this century has been the introduction of medical science to large, undeveloped areas throughout the world. Backward, mainly tropical, regions have become fertile fields for study, particularly of nutritional and parasitic disorders, and the application of the modern biochemical methods have show that many inhabitants of these countries lack certain of the biochemical "normal" values seen in Europeans. One of the most striking differences is that of the serum proteins. Although by no means confined to this continent, these differences are commonly found in Africans.